Reporting a rare form of myopathy, myopathy with extrapyramidal signs, in an Iranian family using next generation sequencing: a case report - Marzieh Mojbafan; Somayeh Takrim Nojehdeh; Faezeh Rahiminejad; Yalda Nilipour; Seyed Hasan Tonekaboni; Sirous Zeinali (BMC, 2020)
Abstract Background Myopathy with extrapyramidal signs (MPXPS) is an autosomal recessive mitochondrial disorder which is caused by mutation in mitochondrial calcium uptake 1 (MICU1) gene located on chromosome 10q22.1. Next Generation Sequencing (NGS) technology is the most effective method for identification of pathogenic variants with the ability to overcome some limitations which Sanger sequencing may encountered. There are few reports on this rare disease around the world and here in this study we first revealed genetic identification of two affected individuals in an Iranian family with a novel mutation. Case presentation The proband was a 5-year-old girl from consanguenous parents. She was first clinically suspicious of affected with limb-girdle muscular dystrophy (LGMD). Muscle biopsy studies and autozygosity mapping, using four short tandem repeat (STR) markers linked to 6 genes of the most prevalent forms of LGMD, ruled out calpainopathy, dysferlinopathy, and sarcoglycanopathis. DNA sample of the proband was sent for NGS. Whole exome sequencing (WES) revealed a novel mutation c.1295delA in exon 13 of MICU1 gene. This homozygous deletion creates a frameshift and a premature stop codon downstream of canonical EF4 calcium binding motif of MICU1. According to the American College of Medical Genetics and Genomics (ACMG) guidline for sequence interpretation, this variant was a pathogenic one. Sanger sequencing in all family members confirmed the results of the WES. Conclusions This study was the first report of MPXPS in Iranian population which also revealed a novel mutation in the MICU1 gene.